2016
DOI: 10.1111/bph.13395
|View full text |Cite
|
Sign up to set email alerts
|

NVP‐TAE684 reverses multidrug resistance (MDR) in human osteosarcoma by inhibiting P‐glycoprotein (PGP1) function

Abstract: BACKGROUND AND PURPOSEIncreased expression of P-glycoprotein (PGP1) is one of the major causes of multidrug resistance (MDR) in cancer, including in osteosarcoma, which eventually leads to the failure of cancer chemotherapy. Thus, there is an urgent need to develop effective therapeutic strategies to override the expression and function of PGP1 to counter MDR in cancer patients. EXPERIMENTAL APPROACHIn an effort to search for new chemical entities targeting PGP1-associated MDR in osteosarcoma, we screened a 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…[15][16][17][18][19][20] There has been much research on the mechanism of MDR in the recent years, 21,22 and scientists are trying to explore the mechanisms to overcome MDR such that chemotherapy drugs could exhibit a higher efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] There has been much research on the mechanism of MDR in the recent years, 21,22 and scientists are trying to explore the mechanisms to overcome MDR such that chemotherapy drugs could exhibit a higher efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that many agents play an important role in reversing MDR by inhibiting the function and expression of P-gp. 39 As shown in Fig. 9a, iso-PXA signicantly increases the intracellular accumulation of Rh123, which conrms that iso-PXA inhibits the efflux function of P-gp.…”
Section: Discussionmentioning
confidence: 80%
“…However, cisplatin resistance is frequently reported, meaning that the enhancement of cisplatin sensitivity is imperative (26). Several studies have reported that inhibition of P-gp reverses drug resistance in OS (27)(28)(29)(30). In the current study, P-gp was found to be overexpressed in cisplatin resistant OS specimens compared to cisplatin sensitive ones.…”
Section: Discussionmentioning
confidence: 99%